2020
DOI: 10.1186/s10194-020-01162-x
|View full text |Cite
|
Sign up to set email alerts
|

Economic consequences of migraine in Sweden and implications for the cost-effectiveness of onabotulinumtoxinA (Botox) for chronic migraine in Sweden and Norway

Abstract: Background Migraine is a common and incapacitating condition, with severe impact on the quality of life (QoL) of the afflicted and their families, and negative economic consequences through decreased workforce participation, reduced functional ability and elevated healthcare costs. This study aimed to describe the economic consequences of migraine in Sweden using cost of illness survey data and, based on this data, assess the cost-effectiveness of onabotulinumtoxinA (Botox) for the treatment of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 28 publications
0
57
0
Order By: Relevance
“…When compared with oral migraine preventive medications, onabotulinumtoxinA was associated with a significantly lower likelihood of headache-related emergency department visits and hospitalizations in a large, United States healthcare claims database study [ 31 ]. Additionally, cost-effectiveness analyses have shown that onabotulinumtoxinA is a cost-effective treatment for chronic migraine in the UK [ 20 , 32 ], Sweden and Norway [ 33 ], and Italy [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…When compared with oral migraine preventive medications, onabotulinumtoxinA was associated with a significantly lower likelihood of headache-related emergency department visits and hospitalizations in a large, United States healthcare claims database study [ 31 ]. Additionally, cost-effectiveness analyses have shown that onabotulinumtoxinA is a cost-effective treatment for chronic migraine in the UK [ 20 , 32 ], Sweden and Norway [ 33 ], and Italy [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Migraine is globally among the leading causes of disability according to the number of years lived with disability metric [1]. This neurological disease particularly affects people in their prime working years and is not only associated with decreased quality of life but also with work impairment resulting in a significant economic burden on societies [2][3][4][5]. Several studies have demonstrated the association between migraine and an increased number of sick leave days, productivity loss and increased health care resource use [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This neurological disease particularly affects people in their prime working years and is not only associated with decreased quality of life but also with work impairment resulting in a significant economic burden on societies [2][3][4][5]. Several studies have demonstrated the association between migraine and an increased number of sick leave days, productivity loss and increased health care resource use [2,[6][7][8]. In one survey, 70% of migraine patients reported that migraine had affected their working life, and 60% of responders reported to have missed at least 1 day of work in the last month due to migraine, with an average of 4.5 days missed in the last month [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients can still use the medication if they still have headache recurrence (botulinum toxin A injection into masseter muscle) [19]. The presence of these symptoms in the early postoperative period, in which we often observe edematous changes in the nose, should not worry either the patient or the surgeon.…”
Section: Treatmentmentioning
confidence: 99%